Modelling the effects of psyllium and water on dough parameters using Mixolab® and their relationship with physical properties and acceptability of gluten-free bread (Research, Society and Development, 2020)
This study aimed to investigate the effects of psyllium (P) and water (W) on dough Mixolab® parameters, and their relationship with gluten-free bread (GFB) physical properties and acceptability. A 2² factorial design with three center points was used, in which P levels ranged from 2.86 to 17.14% and W levels from 82.14 to 117.86% on a flour basis. Samples were compared to a control GFB (0P:100W), and data were evaluated using regression models and multiple factor analysis (MFA). The predicted model equations were significant (R2adj= 82-99%, p